Incidence report of traumatic brain injury in Mimika Public Hospital Papua - Kevin Kristian Putra; Putu Ayu Indra Shanti Wardani; I Wayan Niryana (Intisari Sains Medis, 2021)
Introduction: Traumatic brain injury is a functional brain disorder caused by an external force, which giving persistent consequences, progressive, long-term care, and rehabilitation might be needed. It is also called a “silent epidemic” due to the increased global incidence rate, socio-economic burden, and quality of life. The major cause of TBI was road traffic injury, fall, and blunt trauma.Methods: This research was conducted with a descriptive research design using a prospective cross-sectional design. The research sampling was using medical records in accordance with inclusion and exclusion criteria from 2018 to 2019.Result: The collected sample was 393 cases. There were 66.16% and 67.18% cases occurred to man and productive age with incidence rate 178.89 in 100.000 people. The major cause of TBI was road traffic injury and intentional injury with 58.52% and 24.17% consecutively. The involvement of alcohol in TBI cases was found in 24.42% of cases. The usage of the helmet was not found in 96.6% of cases of RTI.Conclusion: The majority of TBI patients at Mimika Public Hospital in 2018-2019 occurred in men and in the productive age, which was majorly caused by road traffic injury and intentional injury.